Reflecting on Canadian identities: "Canadian Idol" as identity building? - Middlebrook, Ruth E. A (University of Ottawa (Canada), 2009)
This study explores the phenomena of Canadian identity in contemporary Canadian society. It looks at how CTV television show Canadian Idol constructs Canadian identity for its viewers and how they understand Canadian identity. It also looks at whether the representation of Canadian identity on Canadian Idol is reflected or mirrored in its viewers' discussion. Qualitative content analysis, agenda setting and encoding and decoding models are mobilized to examine whether the show sets the agenda for viewers' discussion on Canadian identity, and whether viewers decode the meaning as it is encoded. The results of this thesis reveal that Canadian Idol represents Canadian identity with specific dominant markers, which fuel forum members' discussion. This indicates that most viewers' discussions are motivated by the discourse on the show. Nonetheless, this thesis also finds that Canadian Idol's discourse is not always accepted by all viewers, in the same way, all of the time.
Keywords: Canadian Studies.; Mass Communications.